POLA KEPRIBADIAN MANUSIA PERSPEKTIF AL-QUR'AN: (KAJIAN SURAT AL-BAQARAH AYAT 2 – 14) - Zubairi, Zubairi (STAI Asy-Syukriyyah, 2023)
Islam, a religion embraced by hundreds of millions of Muslims in the world, is a way of life that guarantees the happiness of life for its adherents in this world and in the hereafter. It has one essential joint which functions to guide the straight path. Where the instructions are globally covered in the Qur'an. The formulation of the problem that the author examines is how is the pattern of human personality in the Qur'an Surah Al Baqarah verses 2-14 and how is the character of each human personality in the Qur'an Surah Al Baqarah verses 2-14. While the purpose of this research is to to know, the patterns of human personality according to the Qur'an Surah Al Baqarah verses 2 – 14 and to understand the character of each pattern of human personality according to the Qur'an Surah Al Baqarah verses 2 – 14. While the use of research is to make a contribution thoughts about personality and character that are appropriate and not in accordance with Islamic teachings, and are used as an effort for self-understanding which is expected to foster a noble personality and change a despicable personality. The research method used by the author is a data source, divided into two, namely primary data sources and secondary data sources. Methods of data collection, in this case to obtain data obtained by way of literature study which is pursued by the method of reading source books and analyzing and comparing for further identification and grouping and classified according to their respective characteristics in the form of chapters per chapters to facilitate data analysis. The results showed that the patterns of human personality in the perspective of the Qur'an (Study of Surah Al Baqarah verses 2 – 14) are personality classifications, humans are based on the aspect of aqidah, namely their willingness or rejection of the Qur'an as a way of life. The patterns of human personality in this verse are divided into three forms, namely the personality of the believer, the personality of the disbeliever and the personality of the hypocrite. Each has a different character. A believer is always obedient to Allah and willing to accept the Qur'an as his guide in life, an unbeliever is a person who denies Allah and the existence of the Qur'an. Meanwhile, a hypocrite person is a person who is difficult to identify. Outwardly, he appears to be a believer but inwardly he is a disbeliever.